PENGELOLAAN PEMBELAJARAN KETERAMPILAN MEMBACA CEPAT NASKAH NARASI DI SMP NEGERI 1 SEMARANG - Sofiah, Sofiah (2011)
The objective of this research are (1) to describe the learning activity of student at Junior High School State 1 Semarang in reading fast skill of narration script, (2) to describe the learning activity of teacher at Junior High School State 1 Semarang in reading fast skill of narration script. The research's kind is qualitative research. This research is conducted in Junior High School State 1 Semarang. The main subjects in this research are principal, teacher and student. Data collection method used interview with snowball technique, observation, and documentation. Data analysis is started from (1) data reduction, (2) data display, and (3) drawing conclusion. Data validity test used credibility, transferability, conformability and dependability. The research's results are (1) the student at Junior High School State 1 Semarang is active in reading fast skill of narration script by following the instruction that is given by teacher. The students is read narration script and counted word that they read with stopwatch. The student reads used skimming technique according toe teacher's request. But the way, the students still doing an activity that can pursuing the learning ability of reading fast in narration script such as reading habit by voices, less concentration, less understanding of the content of narration script and also bad habit that is done by students in class. (2) Teacher at Junior High School State 1 Semarang is active in reading fast skill of narration script. The activities are done by using many strategies such as extending the eye's movement, reducing repetition, eliminating the noisy habit, and also increase reading concentration. Teacher at Junior High School State 1 Semarang used skimming technique in learning of narration script, and doing learning activity in language laboratory that which has been attached silencer appliance so that the student is not disturbed from the outside laboratory.